Examination of the Singapore shift in Japan's foreign direct investment in services in ASEAN - Shintaro Hamanaka (Asian Development Bank Institute (ADBI), 2011)
Asia is fast becoming the largest recipient of Japan's foreign direct investment (FDI). Within the Asian region, the Association of Southeast Asian Nations (ASEAN) has been the major investment destination of Japan. In the manufacturing sectors, however, the investment flows from Japan to ASEAN - with Thailand being the largest recipient - has been declining. In contrast, Japan's FDI in the services sectors in ASEAN has been growing rapidly. The recent phenomenon of the Singapore Shift in Japan's FDI in the ASEAN services sectors proves interesting. The prominent strategy of Japanese companies is to establish a commercial presence in Singapore, which they expect to be the hub of Southeast Asia, thereby enabling them to supply services to the entire ASEAN region. The magnitude of the Singapore Shift varies for every services sub-sector. By comparing transport and logistics with finance and insurance industries, this paper considers the critical determinants of the Singapore Shift.
Keywords: F2; F13; F15; 330; Außenwirtschaftspolitik; Direktinvestition; Japan; Singapur; ASEAN-Staaten